The role of social capital in improving community welfare in East Java, Indonesia - Noven Suprayogi, Sakethi Arrow Rulloh, Irham Zaki, (Opción, 2020)
Competition in the business world and the advances throughout the era led to a decline in society's togetherness, mutual ownership, and interest in being involved in organization. Social capital can be a way of overcoming this problem since it has an essential element of trust in building a healthy society or organization. This study aims to determine and analyze the role of social capital in terms of network links, norms, and trust in improving the welfare of the community with the indicator of Maqashid Sharia. The results of this study indicate that social capita under the indicators of norms, networks and trust plays a role in improving people's welfare in terms of sharia Maqashid.